Clinical, radiological, and laboratory predictors of a positive urine lipoarabinomannan test in sputum-scarce and sputum-negative patients with HIV-associated tuberculosis in two Johannesburg hospitals - Lior Chernick; Ismail S. Kalla; Michelle Venter (AOSIS, 2021)
Background: Tuberculosis (TB) is a major cause of mortality in persons living with HIV (PLWH). Sputum-based diagnosis of TB in patients with low CD4 counts is hampered by paucibacillary disease and consequent sputum scarcity or negative sputum results. Urine lipoarabinomannan (LAM) has shown promise in the point-of-care detection of TB in this patient subset but lacks sensitivity, and its exact role in a diagnostic algorithm for TB in South Africa remains to be clarified. Objectives: The objective of this study was to better define the patient profile and the TB characteristics associated with a positive urine LAM (LAM+ve) test. Method: This multicentre retrospective record review examined the clinical, radiological, and laboratory characteristics of hospitalised PLWH receiving urine LAM testing with sputum-scarce and/or negative sputum GeneXpert ® (mycobacterium tuberculosis/resistance to rifampicin [MTB/RIF]) results. Results: More than a third of patients, 121/342 (35%), were LAM+ve. The positive yield was greater in the sputum-scarce than the sputum-negative group, 66/156 (42%) versus 55/186 (30%), P = 0.0141, respectively. Patients who were LAM+ve were more likely to be confused (odds ratio [OR] = 2.2, 95% confidence interval [CI] = 1.2-3.7, P = 0.0045), have a higher median heart rate (P = 0.0135) and an elevated quick sepsis-related organ failure assessment score (≥ 2), OR = 3.5, 95% CI = 1.6-7.6, P = 0.0014. A LAM+ve test was significantly associated with disseminated TB (dTB), P 0.0001, TB-related immune reconstitution inflammatory syndrome (IRIS), P = 0.0035, and abdominal TB, P 0.0001. Laboratory predictors of a LAM+ve status included renal dysfunction, P = 0.044, severe anaemia, P = 0.0116, and an elevated C-reactive protein, P = 0.0131. Of the 12 PLWH with disseminated non-TB mycobacteria cultured from the blood and/or bone marrow, n = 9 (75%) had a LAM+ve result (OR = 5.8, 95% CI = 1.6-20.8, P = 0.0053). Conclusion: Urine LAM testing of hospitalised PLWH with suspected active TB had significant diagnostic utility in those that were sputum-scarce or sputum-negative. A LAM+ve result was associated with dTB, clinical and laboratory markers of severe illness, and TB-IRIS. Disseminated non-tuberculous mycobacterial infection of hospitalised PLWH may also yield urine LAM+ve results, and mycobacterial cultures must be checked in those non-responsive to conventional TB treatment. Selective use of the LAM test in the critically ill is likely to maximise the diagnostic yield, improve the test's predictive value, and reduce the time to TB diagnosis and initiation of treatment.